2020
DOI: 10.1007/978-3-030-39540-7_12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Age Differences in Motivations for and Acceptance of Chatbot Communication in a Customer Service Context

Abstract: This qualitative interview study explores age differences in perceptions of chatbot communication in a customer service context. Socioemotional selectivity theory and research into technology acceptance suggest that older adults may differ from younger adults in motivations to use chatbots, and in perceived complexity and security of this chatbot communication. The in-depth interviews with older adults (54-81 years; N = 7) and younger adults (19-30 years; N = 7) revealed that both groups were aligned in their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 16 publications
1
12
0
1
Order By: Relevance
“…For computer self-efficacy, Lopez et al [45] found a strong negative correlation between people's ages and their self-efficacy with information communication technology 15 . Similarly, van der Groot & Pilgrim, reported that their participants' age influenced their Motivations to interact with technology [77].…”
Section: Results: Cognitive Styles Meet Gender Demographicsmentioning
confidence: 98%
“…For computer self-efficacy, Lopez et al [45] found a strong negative correlation between people's ages and their self-efficacy with information communication technology 15 . Similarly, van der Groot & Pilgrim, reported that their participants' age influenced their Motivations to interact with technology [77].…”
Section: Results: Cognitive Styles Meet Gender Demographicsmentioning
confidence: 98%
“…However, several research studies utilized mixed research methods, such as experimental investigations and questionnaires (e.g. Refs [27,28]) or a combination of interviews and experimental methods [29].…”
Section: Methodsmentioning
confidence: 99%
“…Remarkably, a significant number of researchers have focused on the intention to adopt and use chatbots by investigating factors which affect users in specific research areas, such as health [13], financial services [14][15][16], tourism [5,[17][18][19][20], customer service (e.g. Refs [1,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]), mobile commerce [35][36][37], business [38,39], insurance [12,40] and education [41,42].…”
Section: Users' Intention Toward Chatbots' Adoptionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in 2019, over 50 % of US and German consumers were estimated to have used chatbots at least once-with even higher numbers in the UK or France [88]. In consequence, chatbot researchers currently have an unprecedented opportunity for real-world study of users [106], user motivations [14], and implications at scale. In consequence, knowledge on chatbot use has been gathered for a range of contexts-in the private sphere [87], at work [74], and in public spaces [17].…”
Section: State Of the Artmentioning
confidence: 99%